Pelatihan Dan Pendampingan Legalitas Usaha Untuk UMKM Desa Cupak, Kecamatan Ngusikan, Kabupaten Jombang - Maulidah Narastri; IGN.Andhika Mahendra; Kintania Juaayunata; Estining Kurnia Hadi; Sintha Ayu Pithaloka; Tarenza Noviandari; Aurora Fahriza Pribadi; Dedik Hartawan (Pusat Riset dan Inovasi Nasional, 2023)
Business legality is a standard that must be met by economic entities. Micro, small and medium enterprises (MSMEs) must meet these requirements to compete in the free market era. This requirement is problematic because many business actors do not have business legality. We face various obstacles such as lack of means to ensure legality, difficulty in responding, and lack of knowledge. This paper discusses the results of community service provided, namely assistance and the importance of business legality for MSMEs. The purpose of this service is to raise awareness and provide a framework of thinking about the importance of business legality for MSMEs to compete in the open market. The implementation method used is touse in-depth interviews, observation, and documentation. The result of the implementation is the issuance of a Business Identification Number (NIB) which is the legal umbrella of an official business and recognized by the state through the OSS Institution or known as Online Single Submission.